Proximate Composition, Colour, Texture Profile of Malaysian Chicken Balls - Huda, Nurul; Shen, Yap Hui; Huey, Yong Lin (Pakistan Journal of Nutrition, 2009)
The results of the analyses of six brands of commercial chicken balls showed significant differences (p<0.05) in chemical composition, colour and texture among all samples. Most of the samples contained high moisture content (between 60.14-72.81%), with protein content ranging from a low of 9.93% to moderately high of 15.06%. However, the fat content displayed an inverse relationship as compared to protein, ranging from 4.26-14.00%. The low ash content ranging from 1.92-2.82%, could be contributed by the presence of salts and flavoring ingredients in the chicken balls. The difference in carbohydrate content ranging from 5.54-20.85%, indicated high usage of meat substitute in certain brands tested. The L, a and b values of cooked chicken balls ranged between 69.61-77.96, -2.02 to 0.33 and 15.66-19.70 respectively. The hardness, cohesiveness, springiness and shear force ranged between 3.73-5.73, 0.55-0.69, 11.40- 13.71, 31.27-53.77 and 0.51-1.28, respectively. Chewiness readings obtained were between 31.27-53.77, possibly contributed by the different thickeners used in the formulations. The research result shows that Malaysian commercial chicken balls are significantly different in their chemical composition, colour and textural properties.